Data structure and algorithms using C++ : a practical implementation - Mohanty, Sachi Nandan; Tripathy, Pabitra Kumar (Wiley : Scrivener Publishing, 2021)
"Programming is considered to be basic foundation block for building the logic and skills of the learners. It is also included as one of the fundamental requirements in the course curriculum for engineering students, other graduate disciplines as well as in intermediate classes in school. It is necessary, therefore, for learners to understand the basics to develop the skillset to write programs, design algorithms, digest and apply it in formulating real-world problems. But when the time to write programs comes, most students get scared of and find it hard to learn and score a good mark. There are a number of books available, but keeping the learners' perspective in mind we have set a focal point to reach to the psychology of the students in a layman point of view by introducing and narrating the concepts and syntaxes with the help of simple examples"-- Provided by publisher.
Keywords: Data structures (Computer science); elektronické knihy; electronic books